Knowledge, Attitudes, and Practices Among the General Population During COVID-19 Outbreak in Iran: A National Cross-Sectional Online Survey - Kakemam, Edris; Ghoddoosi-Nejad, Djavad; Chegini, Zahra; Momeni, Khalil; Salehiniya, Hamid; Hassanipour, Soheil; Ameri, Hosein; Arab-Zozani, Morteza (Frontiers in Public Health, 2020)
Background: COVID-19, which emerged in December 2019, is one of the largest pandemics ever to occur. During the early phase, little was known about public knowledge, attitudes, and practices (KAP) relating to Coronavirus disease. This study was designed to determine knowledge, attitudes, and practices (KAP) among the Iranian public towards COVID-19. Methods: A cross-sectional online survey was carried out in Iran from February 25 to April 25 using a self-administered questionnaire on 1,480 people. COVID-19-related KAP questions were adapted from other internationally validated questionnaires specific to infectious diseases. Results: All participants were aware of COVID-19. When asked unprompted, 80% of respondents could correctly cite fever, difficulty breathing, and cough as signs/symptoms of COVID-19. Most of our sample population knew that staying at home and staying isolated (95.3%) as well as constant hand washing and using disinfectants (92.5%) could prevent COVID-19. However, there were also widespread misconceptions such as the belief that COVID-19 can be transmitted by wild animals (58%) and by air (48.3%). Unprompted, self-reported actions taken to avoid COVID-19 infection included handwashing with soap and water (95.4%), avoiding crowded places (93%), cleaning hands with other disinfectants (80.), and covering mouths and noses when coughing and sneezing (76.1 %). The internet and social media (94.5%) were the main Coronavirus information sources. However, the most trusted information sources on Coronavirus were health and medical professionals (79.3%). The majority of participants (77.0%) wanted more information about Coronavirus to be available. Conclusion: Our findings suggest that people's knowledge and attitude towards COVID-19 at the time of its outbreak was of a high level.